Research capacity strengthening for sexual and reproductive health: a case study from Latin America - Kabra, Rita (Reprod Health, 2017)
An essential, but often overlooked part of health promotion and development support to achieve self-sufficiency in developing countries is the concomitant need to build and strengthen research capacity. This is even more challenging and critical in the area of sexual and reproductive health because of diverse interplay of socio cultural, religious, economic factors in relation to reproductive health. This paper presents the case study of HRP’s efforts to build research capacity in Latin America by studying and analyzing the 5-year history of institutional development support to an institution in Paraguay. In reviewing the efforts, we identify the strengths in the approaches used by HRP, the challenges and outcomes of the process and we present recommendations for future efforts to strengthen research capacity to improve sexual and reproductive health. The authors call for greater support from and collaborative efforts of developmental partners and governments to strengthen research capacity in low and middle-income countries to improve sexual and reproductive health. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12978-016-0222-0) contains supplementary material, which is available to authorized users.